2023
DOI: 10.3389/fgene.2022.1033572
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the prognostic value of HK3 and its association with immune infiltration in glioblastoma multiforme

Abstract: Background: Hexokinase 3 (HK3) is one of the key enzymes involved in glucose phosphorylation (the first step in most glucose metabolic pathways). Many studies have demonstrated the vital role of dysregulation of HK3 in several tumors. However, there is a need for in-depth characterization of the role of HK3 in glioblastoma multiforme (GBM).Methods: All data were sourced from The Cancer Genome Atlas (TCGA) and Chinese Glioma Genome Atlas (CGGA). Kaplan-Meier analysis and univariate regression were applied for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 57 publications
(60 reference statements)
0
0
0
Order By: Relevance
“…HK2 is a key enzyme involved in glucose phosphorylation (the first step in the glucose metabolism pathway), and evidence has shown that inhibiting HK2 transcription reduces glycolysis in macrophages ( Yang et al, 2022 ; Yuan et al, 2022 ). S100A8 and S100A9 knockdown inhibited HK2 and GAPDH expression, suggesting that S100A8 and S100A9 are involved in the regulation of glycolysis in allergic asthmatic macrophages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HK2 is a key enzyme involved in glucose phosphorylation (the first step in the glucose metabolism pathway), and evidence has shown that inhibiting HK2 transcription reduces glycolysis in macrophages ( Yang et al, 2022 ; Yuan et al, 2022 ). S100A8 and S100A9 knockdown inhibited HK2 and GAPDH expression, suggesting that S100A8 and S100A9 are involved in the regulation of glycolysis in allergic asthmatic macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…HK1 interacting with S100A8/A9 can blockade glycolysis below GAPDH by nitrosylating GAPDH via nitric oxide synthase 2 (iNOS) ( De Jesus et al, 2022 ). HK1 is an HK isoform and is one of the key enzymes involved in glucose phosphorylation (the first step in the glucose metabolism pathway), which includes HK1, HK2, and HK3 ( Yang et al, 2022 ). It has been suggested that S100A8/A9 can regulate macrophage glycolysis in patients with allergic asthma.…”
Section: Introductionmentioning
confidence: 99%